PERAN SEKOLAH DALAM MENINGKATKAN LITERASI DIGITAL PESERTA DIDIK (STUDI KASUS DI SD MASJID SYUHADA YOGYAKARTA) - Tiara Aulia Mufidha; Arip Febrianto (STKIP Subang, 2026)
This study aims to analyze the role of schools in improving students’ digital literacy at SD Masjid Syuhada Yogyakarta, covering aspects of policies, facilities, and school culture, as well as their integration with religious values. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing.The results show that schools have a strategic role in enhancing digital literacy through well-structured policies, the provision of technological facilities such as Interactive Flat Panel (IFP), and the development of a digital culture based on Islamic values. Teachers act as facilitators and mentors in guiding students to use technology critically, safely, and responsibly. The implementation of digital literacy is not only focused on technical skills but also on character building and digital ethics. Therefore, the institutional role of the school as a whole is proven to be effective in supporting holistic digital literacy development. Keywords: Digital Literacy, School Role, School Culture, Religious Values